Looking for “I”: Casting the Unnamed Heroine in Alfred Hitchcock and David O. Selznick’s Adaptation of Rebecca - Milan Hain (Maison de la Recherche en Sciences Humaines, 2021)
This article considers the lengthy process of casting the unnamed female protagonist in the first film version of Daphne Du Maurier’s Rebecca in light of the more general adaptation strategies employed by the filmmakers, particularly the independent producer David O. Selznick who was renowned for his film versions of literary classics. Drawing on archival documents from the Selznick Collection at the Harry Ransom Center in Austin, Texas, and on the surviving screen tests of several candidates for the main role, the author compares Fontaine’s screen tests with those of her most immediate “rivals” – Vivien Leigh, Anne Baxter, Margaret Sullavan and Loretta Young – and relates them to the vibrant exchange of opinions between Selznick and director Alfred Hitchcock for whom the film marked his Hollywood debut. Furthermore, the text notes how the casting of Joan Fontaine affected the characterization of the second Mrs. de Winter, or “I”, as she is often referred to. By integrating adaptation studies with star and performance studies, the article’s aim is to bring more nuance into the ongoing discussion of this canonical film and its historical relevance.